Analysis Of Tuberculosis Risk Factors Among Children In North Aceh District - khairunnisa, cut (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Tuberculosis is still the most important health problem in the world, which occurs in almost all countries in the world, including Indonesia. Tuberculosis cases in Aceh Province are quite high, reaching 8,471 cases, with North Aceh Regency contributing the most cases with 1,247 cases. There were 240 cases of tuberculosis in children based on this report. Children are a high risk group for contracting TB because their immune systems are not yet optimal. Various risk factors can facilitate the occurrence of TB infection in children, namely, children who are exposed to adults with active TB (positive TB contacts), endemic areas, poverty, unhealthy environments, history of BCG immunization and others. This study aims to find the risk factors that most influence tuberculosis infection in children in North Aceh District. This research used a cohort retrospective research design, sampling was carried out by total sampling with a sample size of 105 in the period 2020 to 2023 at Cut Mutia General Hospital. The results of the study showed that the factors most affected by TB infection in children in North Aceh District were immunization history (p=0.043, OR=5.17) and contact history with a value (p=0.021, OR=7.23. Increased efforts are needed coverage of BCG immunization in children and increasing the cure rate for adult TB sufferers to minimize contact.